Prosthetic Reconstruction of Superior Vena Cava System for Thymic Tumor: A Retrospective Analysis of 22 Cases - Zhang, Zhenglong; Huang, Minhui; Pan, Xiaojie (The Thoracic and Cardiovascular Surgeon, 2020)
Objective This study aimed to report our experience in superior vena cava (SVC) resection and reconstruction for 22 thymic tumor patients and to make comparisons with previous related reports.Methods A retrospective study on 22 patients (15 thymomas, 7 thymic cancers) who underwent tumor resection with concomitant SVC reconstruction. All the patients underwent vascular conduit reconstruction by the cross-clamping technique. The corresponding data were reviewed, including clinical presentation, operation management (surgery procedure, selection of suitable graft, strategies against SVC syndrome, etc.), postoperative cares (antithrombotic agent application, treatments on brain edema, etc.), and follow-up information.Result Two patients were myasthenic, well controlled by oral pyridostigmine. All resections were radical (R0). Ten patients received induction treatment. All the 15 thymoma patients were Masaoka stage III (type B1–B3). As for thymic cancer, six patients were Masaoka stage III and one was stage IVa. Wedge pulmonary resection was performed in three patients (two right upper lobe, one both upper lobe). Procedures included were single graft replacement in 12 patients, bilateral grafts in 9, and Y-shaped graft in 1 patient. Anticoagulation and dehydration agents were routinely applied after operation. No perioperative mortalities were observed. Major complication rate was 9.1%. The median survival time was 44.2 months (range, 4–92 months). Three- and 5-year overall survival rates were 80.8 and 44.0%, respectively. As for conduit patency, two grafts (9.1%) demonstrated evidence of occlusion during long-term follow-up, but no additional interventions were required due to no complications related.Conclusion Our study, confirming data from existing literature, showed that the prosthetic reconstruction of the SVC system is a feasible additional procedure during resection of thymic tumor infiltrating the venous mediastinal axis, minimally increasing postoperative complications in experienced hands.
Keywords: thymus; thymoma; mediastinal tumor; vascular science; biochemistry; pharmacology; pathology